Identification of pheromone components and their binding affinity to the odorant binding protein CcapOBP83a-2 of the Mediterranean fruit fly, Ceratitis capitata - Siciliano, P; He, X L; Woodcock, C; Pickett, J A; Field, L M; Birkett, M A; Kalinova, B; Gomulski, L M; Scolari, F; Gasperi, G; Malacrida, A R; Zhou, J J (Insect biochemistry and molecular biology, 2014)
The Mediterranean fruit fly (or medfly), Ceratitis capitata (Wiedemann; Diptera: Tephritidae), is a serious pest of agriculture worldwide, displaying a very wide larval host range with more than 250 different species of fruit and vegetables. Olfaction plays a key role in the invasive potential of this species. Unfortunately, the pheromone communication system of the medfly is complex and still not well established. In this study, we report the isolation of chemicals emitted by sexually mature individuals during the "calling" period and the electrophysiological responses that these compounds elicit on the antennae of male and female flies. Fifteen compounds with electrophysiological activity were isolated and identified in male emissions by gas chromatography coupled to electroantennography (GC-EAG). Within the group of 15 identified compounds, 11 elicited a response in antennae of both sexes, whilst 4 elicited a response only in female antennae. The binding affinity of these compounds, plus 4 additional compounds known to be behaviourally active from other studies, was measured using C. capitata OBP, CcapOBP83a-2. This OBP has a high homology to Drosophila melanogaster OBPs OS-E and OS-F, which are associated with trichoid sensilla and co-expressed with the well-studied Drosophila pheromone binding protein LUSH. The results provide evidence of involvement of CcapOBP83a-2 in the medfly's odorant perception and its wider specificity for (E,E)-α-farnesene, one of the five major compounds in medfly male pheromone emission. This represents the first step in the clarification of the C. capitata and pheromone reception pathway, and a starting point for further studies aimed towards the creation of new powerful attractants or repellents applicable in the actual control strategies.
Keywords: čich; Male; Protein expression; Fluorescence displacement; fylogeneze; Binding studies; tykadla členovců; sexuální faktory; Odorant binding protein; Phylogeny; Olfaction; Amino Acid Sequence; Pheromone; mužské pohlaví; Medfly; Smell; Electroantennography; Receptors, Odorant; Animals; GC–EAG; ženské pohlaví; receptory pachové; zvířata; Arthropod Antennae; Sex Factors; Pheromone binding protein; elektrofyziologické jevy; Ceratitis capitata; sekvence aminokyselin; Electrophysiological Phenomena; Pheromones; Female; feromony